Pengaruh Investment Opportunity Set, Good Corporate Governance Dan Financial Leverage Terhadap Nilai Perusahaan (Studi Empiris Perusahaan LQ45 Yang Terdaftar Di BEI Periode 2016-2020) - Kinanti Indah Rachmadhita; Yeni Oktaviani (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
This study aims to examine the effect of IOS, GCG and Financial Leverage on firm value with a quantitative approach to 26 LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling method used purposive sampling with predetermined criteria. The data analysis method used was panel data regression analysis with the help of the EViews 9 application. The results showed that IOS had no significant effect on firm value with tcount of 0.389740 with a probability value of 0.6974 > 0.05. GCG as proxy using Managerial Ownership, Institutional Ownership, Board of Commissioners and Audit Committee has no effect on firm value with tcount less than ttable value > 1.97928 with significant value < 0.05. Simultaneously, IOS, GCG and Financial Leverage have no effect on firm value with Fcount 0.213503 < Ftable 2.29 and with a probability value of 0.971933 > 0.05.